High yield seedless synthesis of mini gold nanorods: partial silver decoupling allows effective nanorod elongation with tunable surface plasmon resonance beyond 1000 nm and CTAB-free functional coating for mTHPC conjugation - Rozenberg, Mike; Bárta, Matěj; Muzikansky, Anya; Zysler, Melina; Šišková, Karolína; Mastai, Yitzhak; Zitoun, David (Nanoscale advances, 2024)
Gold nanorods with small dimensions demonstrate better cellular uptake and absorption efficiency. The ability to synthesize gold nanorods while maintaining a tunable high aspect ratio is challenging as it requires careful control of reaction conditions, often employing additional steps such as pH modification or the use of polymeric additives. We demonstrate a seedless approach for the synthesis of mini (width < 10 nm) gold nanorods with tunable longitudinal surface plasmon resonance from ∼700 nm to >1000 nm and aspect ratios ranging from ∼3 to ∼7 without the use of any polymeric additives or pH modification. A single mild reducing agent, hydroquinone, allowed for up to ∼98% reaction yield from a gold precursor. A mechanism for elongation is proposed based on partial silver decoupling from the reaction. Finally, the particles were coated with various capping agents to allow functionalization and conjugation of mTHPC drug molecules, which are used in photodynamic treatments, and cytotoxic CTAB was removed to increase their biocompatibility.